2021
DOI: 10.21203/rs.3.rs-242925/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triggering Factors Associated With a New Episode of Recurrent Acute Anterior Uveitis

Abstract: To identify triggering factors for the next inflammatory episode of recurrent acute anterior uveitis (RAAU), a 1:1 case-control study was conducted. Patients with recent acute anterior uveitis and matched controls were interviewed using Srithanya Stress Test (ST-5) and questionnaires about potential triggering factors. Asymptomatic controls were matched for age (±5 years), sex, and HLA-B27. There were 39 pairs of cases and controls. Within 1-month before the interview, patients who recently experienced a uveit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These findings suggest that patients with uveitis should be actively tested for different etiologies, and that the combination of etiologic and symptomatic treatment results in a faster recovery and better outcomes. Other studies have shown that stress and lack of sleep may contribute to the recurrence of anterior uveitis, while exercise, smoking, and alcohol consumption are not associated with recurrence (22). Other researchers have found that air pollution leads to increased levels of inflammatory cytokines and exacerbates the autoimmune inflammatory response (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that patients with uveitis should be actively tested for different etiologies, and that the combination of etiologic and symptomatic treatment results in a faster recovery and better outcomes. Other studies have shown that stress and lack of sleep may contribute to the recurrence of anterior uveitis, while exercise, smoking, and alcohol consumption are not associated with recurrence (22). Other researchers have found that air pollution leads to increased levels of inflammatory cytokines and exacerbates the autoimmune inflammatory response (23).…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for the treatment of uveitis include glucocorticoids as first-line therapy, immunomodulatory drugs such as cyclosporine A, methotrexate, azathioprine, and Mycophenolate Mofetil as second-line therapy, and biological agents [tumor necrosis factor-alpha antagonists (TNF-α) or interferon-alpha] as third-line therapy (24,25). Neti et al (22) found that slowrelease glucocorticoid injections were rapidly effective in improving visual acuity, with 86% improvement in visual acuity, 27% improvement in pain and 26% improvement in vitreous inflammatory clouding. Posarelli et al (26) found that systemic steroids were used in 42.86% of the patients with uveitis, and the most common ocular complications were cataracts and an increased IOP, but there was no statistical correlation with systemic steroid application.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al [3] found that back pain and stiffness at diagnosis and the presence of complications during the presenting episode of uveitis conferred a higher risk of AAU reactivation (odds ratios 2.29 and 3.86, respectively). Neti et al examined patients with recurrent AAU using questionnaires and found that those with a higher Srithanya Stress Test score and less than seven hours of sleep time had higher chances of recurrences (odds ratio 9.07 and 12.12 respectively) [11]. None of the patients reported eye trauma before AAU reactivation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Neti et al examined patients with recurrent AAU using questionnaires and found that those with a higher Srithanya Stress Test score and less than seven hours of sleep time had higher chances of recurrences (odds ratio 9.07 and 12.12 respectively) [11]. None of the patients reported eye trauma before AAU reactivation [11]. The present case and those previously reported [4][5][6] suggest that trauma may also be a risk factor for the initiation of an AAU episode in HLA-B27 positive patients.…”
Section: Discussionmentioning
confidence: 99%